Incidence, kinetics, and risk factors for intra- and extracranial cerebral arteriopathies in a newborn sickle cell disease cohort early assessed by transcranial and cervical color Doppler ultrasound - Bernaudin, Françoise; Arnaud, Cécile; Kamdem, Annie; Hau, Isabelle; Madhi, Fouad; Jung, Camille; Epaud, Ralph; Verlhac, Suzanne (Frontiers in Neurology, 2022)
The risk of stroke in sickle cell disease (SCD)-children is detected by abnormal intracranial arterial time-averaged-mean of maximum velocities (TAMV≥200 cm/s). Recently, extracranial internal carotid artery (eICA) arteriopathy has been reported and a cross-sectional study showed that eICA-TAMV≥160 cm/s are significantly associated with eICA-kinkings and stenosis. The cumulative incidence and predictive risk factors for intracranial arteriopathy are well described in sickle cell anemia (SCA=SS/S0) but are lacking for SC/S+-children, as is the cumulative incidence of eICA-arteriopathy. We report a prospective longitudinal cohort-study including 493 SCD-children (398 SCA, 95 SC/S+), all assessed by transcranial and cervical color-Doppler-ultrasound. Cerebral MRI/MRA was available in 375 SCD-children and neck-MRA in 365. eICA-kinkings were defined as eICA tortuosities on neck-MRA, with an internal acute angle between the two adjacent segments <90°. Median follow-up was 10.6 years. The cumulative incidence of kinkings was significantly lower in SC/S+ than in SCA children and no SC/S+-child developed intra- or extracranial stenotic arteriopathy. The 10-year KM-estimate of cumulative incidence (95%CI) for eICA-TAMV≥160 cm/s revealed its development in the 2nd year of life in SCA-children, reaching a plateau of 17.4% (13.2-21.6%) by about 10 years of age, while the plateau for eICA-stenosis was 12.3% (8.3-16.3%). eICA-assessment identified 13.5 % (9.3-17.7%) patients at risk of stroke who were not detected by transcranial color-Doppler-ultrasound. We also show for the first time that in addition to a congenital origin, eICA-kinkings in SCD-patients can develop progressively with aging as a function of eICA-TAMVs, themselves related to anemia severity. Ongoing hydroxyurea treatment was significantly associated with lower risk for abnormal intracranial arteriopathy and eICA-kinkings. After adjustment with hydroxyurea, baseline low hemoglobin, high reticulocyte and WBC counts remained independent risk factors for intracranial arteriopathy while low hemoglobin and SEN--haplotype number were independent risk factors for extracranial arteriopathy. The association between extracranial arteriopathy and SEN--haplotype number, suggested a genetic link between ethnic origin and incidence of eICA-kinkings. This prospective cohort-study shows the importance of of systematically assessing eICA and of recording biological parameters during the second year of life before any intensive therapy to predict the risk of cerebral arteriopathy and treat patients with severe baseline anemia